(untitled) (SAARC Journal of Agriculture, 2018)
Mungbean is one of the most important pulse crops due to its nutritive value and maintaining soil fertility through biological nitrogen fixation. Genetic variability is one of the pre-requisite for crop improvement. The present investigation was aimed at to enhance the genetic variability for three quantitative traits viz. pod length, number of seeds per pod and 100-seed weight in M2 and M3 generations of mungbean following mutagenesis with ethylmethane sulphonate (EMS), hydrazine hydrate (HZ) and sodium azide (SA). Mean pod length did not differ significantly in most of the mutagenic treatments in M2. However, significant improvement for the trait was exhibited with lower and moderate concentrations in M3 generation. The mean number of seeds per pod and 100-seed weight increased with lower and moderate concentrations of the mutagens in M2, whereas M3 generation showed a complete positive trend of shift. Long pod and bold seeded mutants may be exploited to increase the number of seeds per pod and seed size leading to increased yield potential. The genotypic coefficient of variation, heritability and genetic advance increased manifold in the treated population for all these traits suggesting that mutagen induced variability has the substantial scope to improve the mungbean crop. SAARC J. Agri., 15(2): 57-67 (2017)